KHIDMAH DALAM PERSPEKTIF AL-QUR’AN DAN URGENSINYA BAGI PARA SANTRI - Setiono, Joko; Rena, Syahidah; Syarif, Fajar (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2022)
Khidmah is a series of acts of service or a loyal attitude to help someone or something with sincerity and totality carried out by chosen people in order to seek the blessings of knowledge and life that have lasted since the time of prophethood. However, the term khidmah in the modern era is often just a jargon to increase popularity or spread imagery to attract public attention and sympathy. This paper aims to describe the process and explore the wisdom of the khidmah tradition which is mentioned implicitly in various verses in the Qur'an so that it becomes clearer so that it is able to provide a complete description and correct understanding. This type of research is descriptive qualitative, with library research data collection through related and relevant literature with the title of this research. The results of this study indicate that khidmah has become a culture carried out by chosen humans as a manifestation of a student's loyalty to his teacher, one's obedience to others, one's gratitude for the blessings he has received, a form of leader service to his community, even being evidence of the creature's obedience to creatures which is not the same kind that is done with full dedication and totality. The culture of khidmah has become a tradition that is inseparable from the values ​​of goodness that help maintain the existence of Islamic values ​​during the time of the Prophet Muhammad and the times after. Khidmah, for santri (the islamic students) has become part of the process of independence and a means of seeking blessings, while for the pesantren (islamic boarding school) it has become an effective medium in the education process and character building for the santri so that their existence continues to be maintained by various methods that adapt to their times